Pasta Consumption Is Linked to Greater Nutrient Intakes and Improved Diet Quality in American Children and Adults, and Beneficial Weight-Related Outcomes Only in Adult Females - Papanikolaou, Yanni (Frontiers in Nutrition, 2020)
Abstract: The present analyses evaluated associations between pasta consumption, nutrient intakes, and diet quality in U.S. children (2-18 years-old; N=323) and adults (≥19 years-old; N=400) using the US National Health and Nutrition Examination Survey, 2001-2012 dataset. An additional aim included assessing associations with pasta consumption and weight-related outcomes in adults. Consumption of dry, domestic and imported wheat pasta/noodles without eggs defined pasta consumers. Energy intake was similar when comparing pasta consumers vs. non-consumers of pasta. Pasta consumers had increased daily intake of dietary fiber (16±0.6 vs. 13±0.1 g/d, p<0.0001; 21±0.8 vs. 16±0.1 g/d, p<0.0001), folate, DFE (701±30 vs. 528±5 µg/d, p<0.0001; 733±42 vs. 546±4 µg/d, p<0.0001), iron (16±0.5 vs. 14±0.1 mg/d, p=0.01; 18±0.9 vs. 16±0.1 mg/d, p=0.01), magnesium (249±7 vs. 231± mg/d, p=0.006; 327±12 vs. 297±2 mg/d, p<0.02), and vitamin E as α-tocopherol (7±0.4 vs. 6±0.05 mg/d, p=0.012; 10.0±0.4 vs. 7.7±0.1 mg/d, p<0.0001), when compared to non-consumers of pasta, in children and adults, respectively. Daily intakes for potassium, calcium, vitamin A and vitamin D were similar when comparing pasta consumers to non-consumers of pasta. Adult pasta consumers had reduced added sugar and saturated fat intake, while no differences were observed for sodium intake vs. non-pasta consumption. Pasta consumption in children was associated with lower saturated fat, with no differences seen in added sugar and sodium intake. Pasta consumption was associated with an improved diet quality relative to non-pasta consumption (children: 48.6±1.0 vs. 45.6±0.2, p=0.002; adult: 51.0±0.9 vs. 48.9±0.2, p=0.024). No associations were observed when evaluating pasta consumption in all adults, however, gender-specific analysis revealed reduced body mass index, waist circumference, and body weight in females aged 19-50 years when compared to no pasta consumption. Overall, pasta consumption was associated with a better diet quality, improved nutrient intakes and lower intake of nutrients to limit relative to non-pasta consumption in Americans.